Pathophysiology of heart failure and frailty: a common inflammatory origin?. Issue 3 (7th March 2017) - Bellumkonda, Lavanya; Tyrrell, Daniel; Hummel, Scott L.; Goldstein, Daniel R.
Summary: Frailty, a clinical syndrome that typically occurs in older adults, implies a reduced ability to tolerate biological stressors. Frailty accompanies many age‐related diseases but can also occur without overt evidence of end‐organ disease. The condition is associated with circulating inflammatory cytokines and sarcopenia, features that are shared with heart failure (HF). However, the biological underpinnings of frailty remain unclear and the interaction with HF is complex. Here, we describe the inflammatory pathophysiology that is associated with frailty and speculate that the inflammation that occurs with frailty shares common origins with HF. We discuss the limitations in investigating the pathophysiology of frailty due to few relevant experimental models. Leveraging current therapies for advanced HF and current known therapies to address frailty in humans may enable translational studies to better understand the inflammatory interactions between frailty and HF.